Evaluation of the limitations of RMR89 system for preliminary support selection in weak rock class - Kanik, Mustafa (Elsevier Sci Ltd, 2019)
Recently, testing the preliminary support elements obtained from the rock mass classification systems with the aid of the numerical analyses give more effective results in terms of safety and estimating the costs. The empirical classification systems have many advantages as well as some limitations. The aim of this study is to evaluate the limitations of the RMR89 for weak rock masses. Within this scope, the rock masses defined as weak rock by using the RMR89 system were examined by the numerical analyses. The investigations were carried out considering the weakest (lower boundary) and the strongest (upper boundary) limits of the weak rock class. According to the results of the analyses, the support elements determined for the weak rock were yielded before reaching the RMR89 system's limitations and the support elements were stable up to a certain depth, depending on the tunnel sizes. It is also revealed that, when determining the preliminary support systems for deeper excavations than the depths defined in this study, the support elements of a lower rock mass class is appropriate to use in the view of safe construction and estimating the costs.
Keywords: Rock mass rating; Numerical analyses; Weak rock; Overburden